2023
DOI: 10.24875/gmm.m18000043
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D deficiency in Mexican mothers and their newborns

Abstract: Objective: The purpose of this study is to establish the prevalence of vitamin D deficiency and their newborns and analyze the risk factors related to this deficiency. Methods: This is an observational, transversal, and prospective study. It included 191 puerperal women and their full-term newborns. Serum 25 hydroxyvitamin D values were analyzes by enzyme immunoassay. Results: 61% of the puerperal presented deficiency and 26% insufficiency of vitamin D. In the newborn group 98% showed deficiency and 66% of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…In Sweden, a longitudinal study reported that 37% of pregnant women in the first trimester had 25(OH)D concentrations < 20 ng/mL [9], compared with 23% of Canadian women [10]. In Mexico, a previous crosssectional study reported vitamin D deficiency among 61% of women in the third trimester, and 98% of their newborns were vitamin D deficient [11].…”
Section: Introductionmentioning
confidence: 99%
“…In Sweden, a longitudinal study reported that 37% of pregnant women in the first trimester had 25(OH)D concentrations < 20 ng/mL [9], compared with 23% of Canadian women [10]. In Mexico, a previous crosssectional study reported vitamin D deficiency among 61% of women in the third trimester, and 98% of their newborns were vitamin D deficient [11].…”
Section: Introductionmentioning
confidence: 99%
“…Dilated cardiomyopathy can occur as a result of a deficiency. This significantly increases the morbidity and mortality in such neonates 9,10,11 .…”
Section: Introductionmentioning
confidence: 99%
“…If the deficiency is not corrected early on, radiological changes such as rachitic rosary and craniotabes, decreased mineralization of bones, rib beading, metaphyseal band of relative lucency, mild cupping, or haziness of the distal end of the ulna or radius can be observed. [7][8][9][10] There are very few studies done on the ideal method of diagnosis of vitamin D deficiency in neonates. Hence, we performed this study to observe the diagnostic potential of cord vitamin D levels in term neonates a well as assessing the maternal factors influencing it.…”
Section: Introductionmentioning
confidence: 99%
“…In Sweden, a longitudinal study reported 37% of first-trimester pregnant women had 25(OH)D concentrations < 20 ng/mL [ 13 ], in comparison with 23% of Canadian women [ 14 ]. In Mexico, a previous cross-sectional study reported VDD among 61% of women in the third trimester, and 98% of their newborns had vitamin D deficiency [ 15 ].…”
Section: Introductionmentioning
confidence: 99%